The Theoretical Origins of Some Gilles Deleuze’s Concepts - Junutytė, Laura (Problemos, 2009)
The article analyzes the conceptions of Benedictus Spinoza and Gotfryd Leibniz, the authors who mostly influenced the ontology of becoming of Gilles Deleuze. The main object of this research is the first Deleuze’s publications about the traditional philosophers who became the basis for creating his original philosophy. The main thesis of this article is that Deleuze’s philosophy is incomprehensible without references to traditional philosophy because his concepts are a result of the transformation of old concepts. In the beginning of the article, the problem of Deleuze’s relationship with classical philosophers is considered: what kind of reasons and motives forced Deleuze to follow the history of philosophy and to choose the authors who avoid the tradition of philosophy? And what method was applied in reading these classical texts?